Intermittent (every-other-day) drinking induces rapid escalation of ethanol intake and preference in adolescent and adult C57BL/6J mice - Melendez, Roberto I. (2011)
BACKGROUND: Using adult C57BL/6J (B6) mice, we previously developed a procedure that causes a progressive increase in ethanol intake and preference (i.e., alcohol escalation effect) following weekly (intermittent) access to ethanol (Melendez et al. Alcohol Clin Exp Res 30, 2006). A limitation of this procedure is that it requires many weeks of testing, which limits its use to study ethanol escalation (i.e., binge-like drinking) during adolescence. Previous studies have shown that intermittent every-other-day (EOD) access to ethanol is sufficient to induce ethanol escalation in rats. The objective of this study was to verify if EOD access is sufficient to induce escalated levels of ethanol intake and preference in adult and adolescent B6 mice. METHODS: Male B6 mice received free-choice 24 hr access to 15% ethanol and water on an EOD or daily basis for 2 weeks. Food and water was available at all times. Using adult mice, Experiment 1 characterized the induction of ethanol escalation following EOD access at 6 (i.e., drinking in the dark) and 24 hr intervals, whereas Experiment 2 determined if daily drinking reverses escalation induced by EOD drinking. Experiment 3 compared ethanol-drinking capacity following daily versus EOD drinking in adolescent (P30–45) and adult (P70–85) mice. RESULTS: Experiment 1 revealed that EOD drinking leads to a significant (nearly two-fold) increase in ethanol intake and preference over mice given daily access. Experiment 2 demonstrated that EOD-elicited escalation is blocked and subsequently reversed following daily drinking. Experiment 3 revealed that ethanol drinking was greater in adolescent mice compared to adults following daily drinking and EOD (escalated) drinking. Although the escalated levels of ethanol intake were greater in adolescent mice, the rate or onset of escalation was comparable between both age groups. CONCLUSIONS: This study is the first to demonstrate that EOD drinking leads to escalation of ethanol intake and preference in adolescent and adult mice. Moreover, our results indicate that daily ethanol reverses ethanol escalation induced by intermittent drinking. The study also revealed that adolescent mice have a greater capacity to drink ethanol under both daily (controlled) and EOD (escalated) conditions, which further supports the notion of adolescent’s susceptibility to heavy drinking.